2020
DOI: 10.2174/1568026620666200516152756
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule CDK Inhibitors for the Therapeutic Management of Cancer

Abstract: : Cyclin-dependent kinases (CDKs) is a group of multifunctional enzymes consisting of catalytic and regulatory subunits. The regulatory subunit, cyclin remain dissociated under normal circumstances, complexation of cyclin with the catalytic subunit of CDK leads to its activation for phosphorylation of protein substrates. The primary role of CDKs is in the regulation of the cell cycle. Retinoblastoma protein (Rb) is one of the widely investigated tumor suppressor protein substrate of CDK, which prevent cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 156 publications
0
17
0
Order By: Relevance
“…Flavopiridol is a CDK inhibitor can have antiproliferative/proapoptotic effects in different cell lines through cell cycle arrest and by reducing c-Myc expression (Cobanoglu et al, 2016;Gokce et al, 2016;Dogan turacli et al, 2019). c-Myc overexpression has been reported in many cancer types including esophageal cancer (Tselepis et al, 2003;Dang, 2012;Jung et al, 2017;Wang et al, 2019) as we reported herein, and inhibiting CDK function using small molecule inhibitors (Senderowicz, 2003;Goel et al, 2020) sensitizing c-Myc overexpressing esophageal cancer cells to induce apoptosis can also be exploited. In this study, we have demonstrated the efficacy C-Myc expression was manipulated pharmacologically and genetically.…”
Section: Discussionmentioning
confidence: 75%
“…Flavopiridol is a CDK inhibitor can have antiproliferative/proapoptotic effects in different cell lines through cell cycle arrest and by reducing c-Myc expression (Cobanoglu et al, 2016;Gokce et al, 2016;Dogan turacli et al, 2019). c-Myc overexpression has been reported in many cancer types including esophageal cancer (Tselepis et al, 2003;Dang, 2012;Jung et al, 2017;Wang et al, 2019) as we reported herein, and inhibiting CDK function using small molecule inhibitors (Senderowicz, 2003;Goel et al, 2020) sensitizing c-Myc overexpressing esophageal cancer cells to induce apoptosis can also be exploited. In this study, we have demonstrated the efficacy C-Myc expression was manipulated pharmacologically and genetically.…”
Section: Discussionmentioning
confidence: 75%
“…USFDA approval of three CDK 4/6 inhibitors viz., palbociclib, ribociclib, and abemaciclib for the treatment of advanced and metastatic breast cancer has already proven the efficacy of this class of molecules as potential anticancer drugs ( Fig. 3 ) [49] . Several CDK inhibitors have been evaluated in preclinical as well as clinical studies for the treatment of HNSCC.…”
Section: Molecular Targeted Therapymentioning
confidence: 99%
“…Median OS was reported to be 9.7 months in palbociclib plus cetuximab group and 7.8 months in cetuximab group, showing a prolongation of median OS in combination group compared to cetuximab alone [53] . Riviciclib (P276–00), a novel inhibitor of CDK 1/4/9 [49] , has been tested in two clinical studies (NCT00899054 and NCT00824343) in advanced HNSCC patients, and results are forthcoming. Flavopiridol, a CDK 4/9 inhibitor, has also completed a phase 2 trial (NCT00020189) focussed on the effectiveness in R/M HNSCC patients.…”
Section: Molecular Targeted Therapymentioning
confidence: 99%
“…However, periodic complexation of a cyclin with its catalytic unit leads to its activation and phosphorylation of a variety of downstream target proteins required for cell cycle progression [10,11]. CDKs regulate cell cycle transitions via phosphorylation and subsequent inactivation of the retinoblastoma (Rb) protein, a tumor suppressor that prevents cell cycle transition [12]. Thus, the inactivation of this Rb protein allows the free flow and progression of cells into the cell cycle, leading to multi-cell cycles, cell proliferation, and eventual development into cancer cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…CDKs regulate cell cycle transitions via phosphorylation and subsequent inactivation of the retinoblastoma (Rb) protein, a tumor suppressor that prevents cell cycle transition [12]. Thus, the inactivation of this Rb protein allows the free flow and progression of cells into the cell cycle, leading to multi-cell cycles, cell proliferation, and eventual development into cancer cells [12].…”
Section: Introductionmentioning
confidence: 99%